# Which expression is equivalent to (4 + 6i)^{2}?

-20 + 48i, 8 + 12i, 16 - 36i, 20 + 48i

**Solution:**

We know that, (a + b)^{2} = a^{2} + 2ab + b^{2}

Given: (4 + 6i)^{2}

Where, a = 4, b = 6i

Then,

= (4)^{2} + 2(4)(6i) + (6i)^{2}

= 16 + 48i + 36i^{2}

= 16 + 48i - 36 (i^{2} = -1)

= -20 + 48i

Therefore, the expression equivalent to (4 + 6i)^{2} is -20 + 48i.

## Which expression is equivalent to (4 + 6i)^{2}?

**Summary:**

The expression equivalent to (4 + 6i)^{2} is -20 + 48i.

Math worksheets and

visual curriculum

visual curriculum